Distributional effects of optimal commodity taxes combined with minimum income programs in Brazil - Ana Luiza Neves de Holanda Barbosa; Eduardo P. S. Fiuza; Marcel Scharth; Seki Asano (Institute for Applied Economic Research (ipea), 2015)
Commodity taxes play an important role in Brazil and raise around 60% of the total tax revenue. This heavy reliance renders commodity taxation one of the main tools available to the government for collecting revenue and securing redistribution. In fact, Brazilian income inequity is one of the highest in the world: the wealthiest 1% of population, equivalent to 1.6 million people, earn together as much as the 50% poorest, around 80 million. The purpose of this paper is a partial equilibrium numerical micro-simulation of the distributional effects of optimal commodity taxation combined with minimum income transfers made by the government to households. The approach used to measure households welfare is a money metric indirect utility or equivalent income [King (1983)], obtained from an Almost Ideal Demand System set of parameter estimates. We plug it into the equivalent variation formula to evaluate the equity effects specified in terms of the equivalent income. The data source is a 1995-1996 national household expenditure survey, though estimated parameters come from a sample comprising a 1987-1988 wave as well. We find that our proposed minimum income programs combined with selectiveness in commodity tax structure would be useful as redistribution income instrument among households in Brazil. These results can provide some valuable contribution in the context of the increasing discussion about minimum income programs in Brazil associated with demographic characteristics such as education and family size.
Keywords: 330